The Role of Personnel Institution in the Implementation of Educative Development Against Female Prisoners - Paga Meka, Kornelius Yoseph; Setiyono, Setiyono; Indrawati, Indrawati (Eduvest - Journal of Universal Studies, 2021)
The change of view in treating prisoners in Indonesia is of course based on a humanitarian evaluation which is a manifestation of Pancasila as the basis for a nation's view of life that recognizes the human rights of prisoners. This research discusses the role of prison officers in the implementation of educational coaching for female prisoners in Class IIA Women's Prison. Kebonsari Malang City. The author uses this type of empirical legal research, which means that this research describes the facts that occur in the field and knows the effectiveness of the enactment of positive law in society. The results of this study the authors found that the role of female prison officers in the implementation of educational coaching for female prisoners in Class IIA Kebonsari Women Penitentiary Malang City includes personality development activities and independence development activities. Personality development is directed at fostering mental and character so that prisoners become fully human, pious and responsible to themselves, their families and society. Development of personality and independence includes matters related to devotion to God Almighty, National and State Awareness, Intellectuals, Attitudes and Behaviors, Physical and Spiritual Health, Legal Awareness, Reintegration with Society, Work Skills, Work Training and Production in accordance with Article 3 Government Regulation Number 31 of 1999.